Computer Telephony Integration, Second Edition - Yarberry, William (CRC Press, 2009)
Since the publication of the first edition, the CTI world has changed significantly. Where it was once focused on the integration of voice systems with computers, the focus is now on IP-based voice, or converged networks and services. Today, the telcos are upgrading their systems from circuit-switched to IP-based packet-switched networks. Companies like Cisco Systems and Dow Chemical have installed IP-based phones in their offices worldwide, saving millions of dollars in service fees.